On development of a monsoon low over northwest India (MAUSAM, 1987)
A case of an unusual formation of a monsoon low pressure area over Rajasthan and neigh-bourhood during its vertical structure and the associated rainfall resemble a typical monsoon depression. Development took place when a mid-tropospheric vortex moved in a southerly direction from the Jammu & Kashmir region and was superposed on the monsoon trough which had moved into Rajasthan due to movement of a Bay depression. The low developed as a downward propagaton of the mid-tropospheric vortex in a manner resembling the formation of a typical monsoon depression over the head Bay of Bengal. The low pressure area caused excessive rainfall over Rajasthan. The low showed an unusual movement initially in an easterly direction giving the impression of being a western disturbance, then in a westerly direction and finally in a southwesterly direction. The movement is examined with reference to the 200 mb flow over the area.